Pengaruh Pemberian Ekstrak Jambu Biji (Psidium guajava) Terhadap Kadar Trigliserida Darah Tikus Putih (Rattus norvegicus) Jantan Galur Wistar Yang Diinduksi Deksametason - MARIA EVANE NAVY CAHAYA PUTRI; NITA PRANITASARI (HANG TUAH MEDICAL JOURNAL, 2018)
Abstract Background Dexamethasone induction may result in increased of both triglyceride synthesis and VLDL plasma level, which contribute to the increase in triglyceride level. Guava (Psidium guajava) consists flavonoid (quercetin) compounds that can inhibit triglyceride synthesis and decrease blood triglyceride level. Method This research used 24 rats divided into 3 groups: group of rats fed with standard food, group of rats induced by 0.13 mg/kgBW dexamethasone for 14 days starting from day 8, and group of rats induced by 0.13 mg/kgBW dexamethasone for 14 days starting from day 8 and received 3 gr/kgBW guava extract for 21 days. On day 22, blood triglyceride level was measured with glycerol blanking method. Result The result of Mann-Whitney U test showed that blood triglyceride level of group of rats induced by dexamethasone ( X =198.25±55.296 mg/dl) was significantly higher (p=0.001) than group of rats fed with standard food ( X =68.50±16.062 mg/dl). Blood triglyceride level of group of rats induced by dexamethasone and received guava extract ( X =98.75±26.778 mg/dl) did not significantly decreased (p=0.487) compared to group of rats induced by dexamethasone ( X =198.25±55.296 mg/dl). Conclusion The conclusion of this research showed that dexamethasone significantly increased blood triglyceride level and guava extract tend to decrease blood triglyceride level because guava consists flavonoid (quercetin) compounds.